Co-Existing with the Earth : Tzu Chi's Three Decades of Recycling - Kazer, William; Her, Rey-Sheng (Hackensack, NJ ; Singapore : World Scientific Publishing Co. Pte. Ltd., 2021)
"The threat from global warming is growing and human activity is a major contributor to the problem. It is clear that we must change our wasteful behavior before it is too late. The Tzu Chi Foundation believes it can make a difference in addressing this critically important challenge. Over the last three decades it has embraced the cause of recycling and conserving resources to ensure a cleaner environment for future generations. Tzu Chi has mobilized tens of thousands of people in this campaign, expanding from Taiwan to 19 countries and territories around the world. Co-Existing with the Earth, Tzu Chi's Three Decades of Recycling tells the story of this uniquely effective grassroots effort and examines the reasons for its success. It also relates the stories of individual recycling volunteers and explains why they chose to join this international movement"--Publisher's website.
t t t t Health in body and mind -- t t t Getting the message out -- t Appendix.
Keywords: Recycling (Waste, etc.); Conservation of natural resources; Environmental protection -- Citizen participation